PENGARUH GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA AUDITOR DENGAN KOMPLEKSITAS TUGAS DAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERATING (STUDI SURVEI PADA KAP DI PEKANBARU DAN PADANG) - Vivi Aurora Mezal; Amir Hasan; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The study was conducted using a survey method. With the aim to empirical evidence that the effect of leadership style to relation job satisfaction with task complexity and locus of control as moderated of Public Accountant Offices in the city of Pekanbaru and Padang. The population in this study were 13 Public accountant offices in the city of Pekanbaru and Padang. Samples taken are 36 respondents. The type of data used is primary data by using questionnaire method of data collection. Data analysis methods are used MRA (moderated regression analysis) with SPSS Version, 17.0. The results of this study indicate that leadership style effect on the job satisfaction with a t-value of 3,961, 2,032 T-table, a significant 0.000. Leadership style affect on the job satisfaction with moderated by task complexity with a t-value of- 2,603, 2,035 t-table, significant 0.014. Leadership style affect on the job satisfaction with moderated by locus of control with a t-value of 2,296, 2,035 t-table, a significant 0.028.Keywords: Leadership style, task complexity, locus of control and job satisfaction